The Relative Frequency Of Small Vessel Cerebrovascular Disease And Brain Atrophy In MRI Of Patients With Psoriasis - Sahar Dadkhahfar; Mozhdeh Gheisari; Zahra Mahboubi-Fooladi; Mohahmmad Shahidi Dadras (Dermatology Practical & Conceptual, 2023)
Introduction: Psoriasis is a systemic autoimmune disease that is associated with numerous comorbidities.